2019
DOI: 10.1039/c8sm01372a
|View full text |Cite
|
Sign up to set email alerts
|

Betweenness centrality as predictor for forces in granular packings

Abstract: A load applied to a jammed frictional granular system will be localized into a network of force chains making inter-particle connections throughout the system. Because such systems are typically under-constrained, the observed force network is not unique to a given particle configuration, but instead varies upon repeated formation. In this paper, we examine the ensemble of force chain configurations created under repeated assembly in order to develop tools to statistically forecast the observed force network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…We aim to use our insight into the force network to investigate the physical mechanisms that drive nonlocal effects in experiments at low-intermediate values of I where such non-local effects are becoming relevant. In addition, we test whether the shear rate is an appropriate variable in the description of fluidity at all, given that even for static granular packings, force chain configurations are not solely determined by particle positions 36,37 . Instead, there is a force network ensemble (FNE) which can fluctuate independent of, and in addition to, particle rearrangements under shear.…”
Section: Introductionmentioning
confidence: 99%
“…We aim to use our insight into the force network to investigate the physical mechanisms that drive nonlocal effects in experiments at low-intermediate values of I where such non-local effects are becoming relevant. In addition, we test whether the shear rate is an appropriate variable in the description of fluidity at all, given that even for static granular packings, force chain configurations are not solely determined by particle positions 36,37 . Instead, there is a force network ensemble (FNE) which can fluctuate independent of, and in addition to, particle rearrangements under shear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while their shear modulus vanishes at the jamming point, their bulk modulus remains finite [30], which is rather different from, for example, central-force spring networks where both the bulk and shear modulus vanish at their equivalent jamming point [32]. Our networks are generated from real, frictional packings [35] drawn from experiments on uniaxially compressed quasi-2D bidisperse granular packings of frictional photoelastic disks, created using the techniques described in [28,[36][37][38]. In each case, the test structure has a geometry defined by the binary contact network of these disks.…”
mentioning
confidence: 99%
“…Combined with [36,37], our work provides evidence that betweenness centrality successfully identifies physical properties in both granular packings and lattices that are derived from them. Similarly, analyses inspired by rigidity percolation in granular materials have identified that our disordered lattices undergo a ductile-brittle failure transition as a function of connectivity z 0 , as determined by counting degrees of freedom and constraints [38].…”
Section: Discussionmentioning
confidence: 84%